2013
DOI: 10.1093/toxsci/kft176
|View full text |Cite
|
Sign up to set email alerts
|

A Multifactorial Approach to Hepatobiliary Transporter Assessment Enables Improved Therapeutic Compound Development

Abstract: The bile salt export pump (BSEP) is expressed at the canalicular domain of hepatocytes, where it serves as the primary route of elimination for monovalent bile acids (BAs) into the bile canaliculi. The most compelling evidence linking dysfunction in BA transport with liver injury in humans is found with carriers of mutations that render BSEP nonfunctional. Based on mounting evidence, there appears to be a strong association between drug-induced BSEP interference and liver injury in humans; however, causality h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
252
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(280 citation statements)
references
References 37 publications
21
252
5
Order By: Relevance
“…Only 2 VEGFR & PDGFR and 1 BCR/ABL kinase inhibitors were found to be clinically relevant. Similar to the report of Morgan, et al, pazopanib was identified as having the potential for clinically relevant MRP4 inhibition [35]. Additionally, though the studies of Morgan, et al, also identified gefitinib as a potent inhibitor of MRP4, gefitinib-mediated inhibition of MRP4 transport activity was not deemed clinically relevant [35], which is similar to the current results.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Only 2 VEGFR & PDGFR and 1 BCR/ABL kinase inhibitors were found to be clinically relevant. Similar to the report of Morgan, et al, pazopanib was identified as having the potential for clinically relevant MRP4 inhibition [35]. Additionally, though the studies of Morgan, et al, also identified gefitinib as a potent inhibitor of MRP4, gefitinib-mediated inhibition of MRP4 transport activity was not deemed clinically relevant [35], which is similar to the current results.…”
Section: Resultssupporting
confidence: 87%
“…Similar to the report of Morgan, et al, pazopanib was identified as having the potential for clinically relevant MRP4 inhibition [35]. Additionally, though the studies of Morgan, et al, also identified gefitinib as a potent inhibitor of MRP4, gefitinib-mediated inhibition of MRP4 transport activity was not deemed clinically relevant [35], which is similar to the current results. The majority of the TKI/AKIs investigated were found to potentially be clinically relevant inhibitors of BCRP, with 15 of the 20 compounds having a C ss /IC 50 ratio >0.1.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations